Subsurface Structural Identification and Seismicity Correlation in West Java Using EMAG2 Geomagnetic Data - Rayhan Irfan Hielmy (Yayasan Kita Menulis - JoCPES, 2025)
West Java represents one of Indonesia's most seismically active regions, characterized by complex interactions between the Indo-Australian subduction zone and active onshore fault systems. This study investigated subsurface geological configurations and their relationship to earthquake occurrences using Earth Magnetic Anomaly Grid (EMAG2) data with a 2-arc-minute resolution. The research methodology utilized Reduction to the Pole (RTP) to eliminate dipolar effects caused by the equatorial location, followed by spectral analysis to separate regional and residual anomalies. To precisely map structural lineaments, First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) techniques were applied to the residual data. The processed maps revealed distinct anomaly contrasts, with high magnetic intensities (up to 300 nT) associated with volcanic intrusions and low anomalies (approximately −100 nT) indicating sedimentary basins or hydrothermally altered zones. A critical analysis of the December 15, 2017, Tasikmalaya earthquake (Mw 6.5) identified a strong correlation between the epicenter and a significant low magnetic anomaly zone of −150 nT. This specific signature was interpreted as a fracture zone characterized by rock demagnetization resulting from tectonic stress accumulation. These findings confirm that integrating EMAG2 data with derivative filtering is a robust approach for delineating active tectonic structures, thereby contributing essential data for regional seismic hazard mitigation.